Roles of Fe–S proteins: from cofactor synthesis to iron homeostasis to protein synthesis. (June 2016) - Pain, Debkumar; Dancis, Andrew
Abstract : Fe–S cluster assembly is an essential process for all cells. Impairment of Fe–S cluster assembly creates diseases in diverse and surprising ways. In one scenario, the loss of function of lipoic acid synthase, an enzyme with Fe–S cluster cofactor in mitochondria, impairs activity of various lipoamide-dependent enzymes with drastic consequences for metabolism. In a second scenario, the heme biosynthetic pathway in red cell precursors is specifically targeted, and iron homeostasis is perturbed, but lipoic acid synthesis is unaffected. In a third scenario, tRNA modifications arising from action of the cysteine desulfurase and/or Fe–S cluster proteins are lost, which may lead to impaired protein synthesis. These defects can then result in cancer, neurologic dysfunction or type 2 diabetes.